Developing a Feasible Integrated Framework for Occupational Heat Stress Protection: A Step Towards Safer Working Environments - Gourzoulidis, Georgios; Gofa, Flora; Ioannou, Leonidas G.; Konstantakopoulos, Ioannis; Flouris, Andreas D. (La Medicina del Lavoro, 2023)
Background: Specialized occupational health and safety (OHS) issues are covered at the EU level through detailed legislation and guidelines. Unfortunately, this does not extend to occupational heat stress, not only in Greece but also (with few exceptions) internationally. One possible explanation could be the difficulty in accurately identifying the dangerous conditions, as many environmental and individualized elements are involved, and hundreds of "thermal stress indicators" are available. Another explanation could be the difficulty in adequately measuring hazardous conditions for workers affected more (i.e., outdoor and high intensity) since the biological protection framework is based on the human body’s internal temperature. Methods: The Wet Bulb Globe Temperature (WBGT) has been proposed as the most efficacious thermal stress indicator. Since 2021, the Hellenic National Meteorological Service has provided 48-h WBGT forecast predictions to serve as a first level of alert. Real-time measurements and 48-h forecasts of WBGT are also available through a smartphone application. Additionally, as revealed when developing the occupational heat stress legislation in Cyprus and Qatar, crucial first steps are identifying the specific characteristics of worker exposure and the tripartite collaboration between employers, workers, and the State. Results: Evaluating the simplified WBGT forecasted values and the smartphone application estimates proved well-established. The sound scientific basis can be effectively combined with administrative measures based on the EU OHS legislative experience to produce practical solutions. Conclusions: As the climate crisis exacerbates, worker productivity and well-being will decline, underscoring the urgent need for an integrated protection framework. Such a framework is proposed here.